The Extent and Impact of Variation in ADME Genes in Sub-Saharan African Populations - da Rocha, Jorge E. B.; Othman, Houcemeddine; Botha, Gerrit; Cottino, Laura; Twesigomwe, David; Ahmed, Samah; Drögemöller, Britt I.; Fadlelmola, Faisal M.; Machanick, Philip; Mbiyavanga, Mamana; Panji, Sumir; Wright, Galen E. B.; et al. (Frontiers in Pharmacology, 2021)
Investigating variation in genes involved in the absorption, distribution, metabolism, and excretion (ADME) of drugs are key to characterising pharmacogenomic (PGx) relationships. ADME gene variation is relatively well characterised in European and Asian populations, but data from African populations are under-studied. We identified significant ADME gene variation in African populations using data from 458 high-coverage whole genome sequences (412 of which are novel) and from previously available African sequences from the 1000 Genomes Project (KGP). ADME variation was not uniform across African populations, particularly within high impact coding variation. Copy number variation (CNV) was detected in 116 ADME genes, with equal ratios of duplications/deletions. We identified 930 potential high impact coding variants, of which most are discrete to a single African population cluster. Large frequency differences (i.e. >10%) were seen in common high impact variants between subgroups. Several novel variants would have a significant impact on protein structure, but additional functional work is needed to confirm the outcome of these for PGx use. For variants of known clinical outcome, we note that most of these are rare in Africa compared to European populations, potentially reflecting a clinical PGx research bias to European populations. PGx strategies based on European variants will be of limited use in African populations. Significant differences were also observed between African population clusters, with the Southern African population cluster most distinct from that of far West Africa. Although established variants are important, PGx must take into account the full range of African variation. This work urges further characterisation of variants in African populations including in vitro and in silico studies, and to consider the unique African ADME landscape when developing precision medicine guidelines and tools for African populations.